The Influence of Phosphate Mining on the Chemical Composition of Annual Atmospheric Deposition in Catalão (GO) and Tapira (MG), Brazil - Da Conceição, Fabiano Tomazini [UNESP]; Litholdo, Taise [UNESP]; De Souza Sardinha, Diego; Moruzzi, Rodrigo Braga [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP]; Godoy, Letícia Hirata [UNESP] (Springer Nature, 2016)
Brazil is an important country within the global mineral industry. The main reserves of phosphate rock in Brazil are contained in the states of Goiás and Minas Gerais, at the Catalão and Tapira cities, respectively. Atmospheric inputs due to the mining of phosphate rock may have various effects on human health in areas near these types of mines. Thus, this work evaluated the influence of phosphate mining on the chemical composition and annual atmospheric deposition in Catalão (GO) and Tapira (MG), Brazil. The pH of rainwater was 6.90 in Catalão and 6.80 in Tapira. The ionic concentrations (in μeq/L) at both study sites decreased in the following order: Ca2+ > Na+ > Mg2+ > K+ for cations and HCO3 - > NO3 - > SO4 2- > PO4 3- > F- > Cl- for anions. High Ca2+ content indicates that Ca2+ contributes to the neutralisation of the rainwater pH in both of the areas studied. The annual atmospheric deposition of NO3 - and SO4 2- can be attributed to the use of diesel-powered trucks in and around mining areas. Soil dust derived is responsible for the annual atmospheric deposition of Na+ and K+. Phosphate mining activities are the main source of the annual atmospheric deposition of PO4 3- and F-.
Keywords: Atmospheric environment; Brazil; Mining activities; Rainwater composition